HUBUNGAN USIA IBU, PARITAS, DAN KADAR HEMOGLOBIN TERHADAP KEJADIAN KETUBAN PECAH DINI DI RUMAH SAKIT UMUM DAERAH TANJUNG PURA - MUHAMMAD FAUZUN TRISNA FIANDI; RAHMANITA SINAGA (JURNAL ILMIAH MAKSITEK, 2023)
According to the 2017 IDHS, in Indonesia the Maternal Mortality Rate is still quite high, namely 228 per 100,000 live births. One of the causes of maternal death is infection which can be caused by premature rupture of the membranes. Risk factors associated with premature rupture of membranes include maternal age <20 and> 35 years, multiparity, anemia, and gemelli. to determine the relationship between maternal age, parity, and hemoglobin levels on the incidence of premature rupture of membranes. Analytical descriptive using cross sectional design with simple random sampling technique. The population of all mothers who gave birth at the Tanjung Pura Hospital from June 2015 to June 2020. The research data were obtained from secondary data which were taken using medical records. Then do the analysis with the Chi Square test. The results of the Chi Square test showed that there was a significant relationship between parity and premature rupture of membranes with a value of p = 0.001. There was no significant relationship between maternal age and hemoglobin levels with the incidence of premature rupture of membranes with p = 0.481 and p = 0.367. There is a significant relationship between parity and the incidence of premature rupture of membranes.